Tales from Kentucky sheriffs - Montell, William Lynwood, 1931- (University Press of Kentucky, 2011)
Following the success of his collections of stories from funeral directors, schoolteachers, doctors, and lawyers, folklorist William Lynwood Montell presents a new volume of tales from Kentucky sheriffs. Montell collected stories from all areas of the state to represent the diversity of social and economic backgrounds in the various communities the officers serve. Tales from Kentucky Sheriffs covers elections, criminal behavior, and sheriff's mistakes in a lighthearted and often humorous manner. The book includes accounts of a drunk driver who thought he was in a different state, a sheriff runn.